AKIBAT HUKUM PENGALIHAN SEWA OBJEK JAMINAN FIDUSIA DARI SUDUT KAJIAN HUKUM PIDANA BERDASARKAN PUTUSAN PENGADILAN NEGERI TANJUNGKARANG KELAS IA NOMOR : 831/PID.SUS/2021/PN.TJK - Vidianti Putri (Maleo Law Journal, 2023)
Fiduciary guarantees are material guarantees for movable objects, both tangible and intangible in connection with accounts payable between debtors and creditors. The problem in this study is what are the factors that cause the perpetrator to commit the crime of transferring the lease of the object of fiduciary security from the point of view of criminal law studies and what are the legal consequences for the perpetrator of the crime of transferring the lease of the object of fiduciary security from the point of view of criminal law studies. The research method used is normative juridical. The factor causing the perpetrator to commit a criminal act of transferring the lease of the object of the fiduciary guarantee without prior written approval from the fiduciary recipient is because the defendant is pressed for economic needs to meet his life needs, so that he is able to make the defendant act beyond the limit, namely the defendant is able to commit a crime only to meet his life needs and the intention factor The crime is greater where the defendant does not have good faith towards the fiduciary object.